Experimental investigation and simulation of catalytic converter performance - Mohiuddin, A. K. M.; Nurhafez, Muhammed (2005)
The purpose of this paper is to present the results of an experimental study of the performance and conversion efficiencies of ceramic monolith three-way catalytic converters (TWCC) employed in automotive exhaust lines for the reduction of gasoline emissions. Two ceramic converters of different cell density, substrate length, hydraulic channel diameter and wall thickness were studied to investigate the effect of varying key parameters on conversion efficiencies and pressure drop. Based on the emission test results, the conversion efficiencies from both converters were calculated and evaluated. Simulation program using commercial computational fluid dynamics (CFD) software packages, GAMBIT and FLUENT 6.1 was used to verify experimental results.